A comparison of mdma-assisted psychotherapy to non-assisted psychotherapy in treatment-resistant PTSD: A systematic review and meta-analysis. (13th April 2021) - Illingworth, B.; Lewis, D.; Lambarth, A.; Stocking, K.; Duffy, J.; Jelen, L.; Rucker, J.
Abstract : Introduction: Novel, evidence-based treatments are required for treatment-resistant post-traumatic stress disorder (PTSD). 3, 4-Methylenedioxymethamphetamine (MDMA) has beneficially augmented psychotherapy in several small clinical trials. Objectives: To review the use of MDMA-assisted psychotherapy in treatment-resistant PTSD. Methods: Systematic searches of four databases were conducted from inception to February 2020. A meta-analysis was performed on trials which were double-blinded, randomised, and compared MDMA-assisted psychotherapy to psychotherapy and placebo. The primary outcomes were the differences in Clinician Administered PTSD Scale (CAPS-IV) score and Beck's Depression Inventory (BDI). Secondary outcome measures included neurocognitive and physical adverse effects, at the time, and within seven days of intervention. Results: Four randomised controlled trials (RCTs) met inclusion criteria. When compared to active placebo, intervention groups taking 75mg (MD -46.90; 95% CI -58.78, -35.02), 125mg (MD -20.98; 95% CI -34.35, -7.61) but not 100mg (MD -12.90; 95% CI -36.09, 10.29) of MDMA with psychotherapy, had significant decreases in CAPS-IV scores, as did the inactive placebo arm (MD -33.20; 95% CI -40.53, -25.87). A significant decrease in BDI when compared to active placebo (MD -10.80; 95% CI -20.39, -1.21) was only observed at 75mg. Compared to placebo, participants reported significantly more episodes of low mood, nausea and jaw-clenching during sessions and lack of appetite after seven days. Conclusions: These results demonstrate potential therapeutic benefit with minimal physical and neurocognitive risk for the use of MDMA-assisted psychotherapy in TR-PTSD, despite little effect on Beck's Depression Inventory. Better powered RCTs are required to investigate further. Disclosure: James Rucker has attended trial related meetings paid for by Compass Pathways Ltd.